Rekonstruksi Desain Kegiatan Laboratorium Pengaruh Bahan Pencemar terhadap Gerak Operkulum Ikan - Mahmudah Nur Cahyaningrum; Bambang Supriatno (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Advancement of times requires students to be able to master life skills. These skills can be improved through improving the learning process in the classroom, one of which is through practicum.Practicum activities carried out at school are still not optimal and have obstacles. Based on analysis in the field, one of the obstacles to the implementation of practicum is the existence of practicum worksheet which has not been able to help students do practicum meaningfully. This research was conducted to provide alternative worksheet that can construct student knowledge so that it can be a good worksheet recommendation to improve students' cognitive abilities, attitudes and skills. The 5 worksheet of polluted material that was studied both quantitatively and qualitatively in the research technique used descriptive qualitative analysis with ANCOR.The results showed that generally worksheet still requires improvement . worksheet t has not raised the object of phenomena that can construct students' knowledge. The recommended alternative worksheet is made by considering the results of the analysis and findings during the trial, consulting with experts and testing the reconstructed worksheet to get worksheet which can be an alternative to practicum activities on environmental change material with an independent curriculum in high school. Keywords: ANCOR, worksheet, pollution